Intersectional Identity and Representation of a Young Girl in Elemental of Force of Nature (2023): A Contemporary Literary Analysis - Qotrunnada, Nabillah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This study analyzes the representation of intersectional identity in the character Ember Lumen from Pixar’s film Elemental (2023), which expresses the complexity of race, gender, and social class dimensions in the life of a minority girl within an immigrant family. The background of this research highlights the significance of children’s films as a narrative arena capable of illustrating and reproducing the dynamics of social patriarchy and structural discrimination that restrict the freedom and self-identity construction of young women. The objective of this study is to describe how Ember’s character embodies acts of resistance against social and cultural pressures through the lens of Kimberlé Crenshaw’s intersectionality theory. A qualitative descriptive approach is employed using the critical film study method to analyze symbols, characters, and narrative elements in the film, focusing on their interactions within socio-cultural contexts. The findings reveal that Ember Lumen successfully resists familial patriarchy and socio-economic constraints to create personal agency and achieve identity transformation. This transformative process signifies a struggle for liberation from traditional norms and socially constructed gender roles within both family and society. The conclusion emphasizes that children’s films can function as a space for social critique and as a medium for gender emancipation among minority women. The implications of this research open new opportunities for developing studies on gender representation and intersectionality in popular media while enriching contemporary literary and children’s film theory.